Voyage of the basset fire bird - Zambreno, Mary Frances, 1954. (New York : Random House, 2001)
Thirteen-year-old Emily, her blind engineer father, and a boy from their English village sail aboard the magic ship Basset to an island of mythical animals, where they use faith and imagination to try to restore a legendary lighthouse tower.
All age.
Keywords: Magic -- Fiction; Lighthouses -- Fiction; Mythology, Classical -- Fiction; Animals, Mythical -- Fiction; Faith -- Fiction; Imagination -- Fiction; Fathers and daughters -- Fiction